Illinois Pharmacists and Over the Counter Cannabidiol Products: A Survey on Knowledge and Educational Needs - Kayla Link; Maithili Deshpande; McKenzie Ferguson (University of Minnesota Libraries Publishing, 2020)
Objective: To assess Illinois pharmacists' (1) baseline knowledge of CBD and self-rated competency of OTC-CBD product pharmacotherapy, (2) concerns about OTC-CBD product safety and level of preparedness with answering questions about the product, and (3) current and future interest in learning more about these types of products to target an area of need for continuing education in the pharmacy field. Design: This observational cross-sectional study used a quantitative survey to obtain information about Illinois pharmacists' knowledge, concerns and educational needs about OTC-CBD products. Survey questions were based on prior research and pilot tested for clarity and completeness. Descriptive statistics were utilized to assess all data. Setting and Participants: The study researchers collaborated with two state-based pharmacy organizations to distribute the survey online with up to two reminders. Results: A total of 181 participants completed the survey. Majority of the respondents were 31-60 years of age, had worked in pharmacy for less than 5 years, in a geographic location with a population of 50,000 or more. About 41% worked in hospital-based practice setting and 39.2% work in a community-based setting. Most pharmacists (64.1%) reported ever being asked about the safety or efficacy of cannabidiol containing products, and only 20.7% responded that they felt moderately/highly prepared to provide medication counseling to patients who use OTC-CBD products. Majority of respondents reported being concerned about safety, quality, and regulations related to OTC-CBD products. Almost all respondents indicated that information about state (90.5%) and federal (89.4%) laws related to CBD, and safety (99.5%) were preferred topics for future education. Conclusions: Consumers are seeking information about CBD containing products; however, many pharmacists do not feel prepared when it comes to being the drug expert for these products. Educational opportunities are necessary for pharmacists to become more comfortable and knowledgeable regarding safe and effective use of CBD-OTC containing products.